Developing Digital Literacy For Vietnamese Civil Servants - Hoan, Dao Manh (Journal of Ecohumanism, 2024)
Different political, economic, cultural and social conditions will lead countries to their own ways, methods and roadmaps to successfully implement their national digital transformation goals. However, there is one factor that always plays a prerequisite role in digital transformation: the human factor - digital literacy. In the public sector, it is the civil servants ‘digital literacy, an essential factor, enables civil servants to achieve the goal of digital transformation, perform public duties in the digital environment and modernize the public administration. In this study, the theoretical framework on digital literacy has been built up, including: (1) Capacity to use digital technology, (2) Capacity to exploit digital information and data, (3) Capacity to create digital content, (4) Capacity to perform digital transactions, assess the impact of digital literacy on civil servants’ public duty performance in the digital environment. A survey was conducted to collect opinions of 360 commune-level civil servants in 3 provinces representing 3 regions of Vietnam, including: Thai Binh province (Northern region), Quang Nam province (Central region), Tay Ninh province (Northern region), Quang Nam province (Central region), Tay Ninh province (Southern region). The results show that the commune - level civil servants self-assess themselves at a low level in terms of proficiency in all four aforementioned digital capacities, posing requirements for the development and implementation of training policies on digital literacy for civil servants in Vietnam today. These findings suggest related issues as recommendations for developing and improving policies on Vietnamese civil servants’ digital literacy.